Is personal insecurity a cause of cross-national differences in the intensity of religious belief? - Rees, Tomas J. (The journal of religion & society, 2009)
Previous research has shown an apparent relationship between “societal health” and religiosity, with nations that exhibit higher mean personal religiosity also tending to provide worse social environments. A possible cause is that exposure to stressful situations (i.e. personal insecurity) increases personal religiosity. To test this hypothesis, income inequality, a widely available proxy for personal insecurity, was compared with other macro-scale causes of religiosity (derived from modernization and rational choice theories) in a multinational, cross-sectional analysis. Income inequality, and hence personal insecurity, was found to be an important determinant of religiosity in this diverse sample of nations.